Ethical Implications of AI in Consumer Behavior Prediction (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has rapidly become a significant tool in predicting consumer behavior, providing businesses with profound insights into purchasing patterns, preferences, and decision-making processes. These predictive models offer valuable data that can be leveraged to personalize consumer experiences, enhance marketing strategies, and optimize product offerings. However, the increasing use of AI in consumer behavior prediction raises serious ethical concerns related to privacy, autonomy, bias, and transparency. This paper examines the ethical implications of AI in predicting consumer behavior, focusing on the risks associated with data privacy, algorithmic bias, and the potential for exploitation of vulnerable populations. By reviewing existing literature, case studies, and theoretical frameworks, the paper aims to highlight the balance between the benefits and ethical challenges posed by AI in this context. The findings suggest that while AI can significantly enhance consumer engagement and business profitability, it also necessitates stringent ethical guidelines to ensure that consumer rights and fairness are not compromised. The paper concludes by offering recommendations for improving AI ethics in consumer behavior prediction through increased transparency, accountability, and ethical AI design.